A SEVEN-YEAR-OLD CHILD WITH HER ENGLISH VOCABULARY ACQUISITION: A CASE STUDY ON NISRINA WAFA ADLINA - Nur, Maulidia Rachmawati (JURNAL PEDAGOGY, 2014)
Abstract: English has become one of the most-frequently used languages at an international level. As a matter of fact English is learned by many people, both adults and young learners. With regard to young learners of English in particular, they are learning English because they want (or they are encouraged) to master English when they are still in their early childhood. Compared to adults, young learners are more likely to achieve automaticity in producing English as a second language (ESL).This research was aimed to see a seven-year-old girlâs English vocabulary acquisition process that she got from her mother, as the researcher. This research was also aimed to see her English vocabulary production that she produced for almost three months.Â Keyword: Second Language Acquisition, vocabulary production, ESL young learner